Effect of persistence in soil of Sulfosulfuron on fababean, chickpea and lentil grown in rotation in semi-arid area - B, Hajjaj; A, El Oualkadi (International Journal of Environment, Agriculture and Biotechnology, 2019)
Abstract: A trial was conducted in greenhouse during 2009-2010 growing season in Chaouia semi-arid area of Morocco in order to study effect of Sulfosulfuron persistence in soil on fababean, chickpea and lentil grown in rotation. Three food legumes were grown in greenhouse pots: fababean, chickpea and lentil. Food legumes seeds were sown in five filled with soil taken from a plot that had been treated the previous year with Sulfosulfuron. Results showed that the highest Sulfosulfuron phytotoxicity was observed on lentil recording 60.8% of phytotoxicity. Phytotoxicity observed on chickpea and fababean pots registered 41.6% and 37.6%, respectively. Thus, intensive tillage is recommended to farmers of Chaouia semi-arid region of Morocco when fababean, chickpea and lentil crops are grown in rotation after cereals, which had been treated with Sulfosulfuron.